Do outcomes from a behavioral weight loss intervention differ in Alabama versus Colorado?. (20th December 2021) - Clina, Julianne G.; Sayer, R. Drew; Cohen, Caroline W.; Wyatt, Holly R.; Baidwan, Navneet Kaur; Hill, James O.
Abstract: Background: There are well‐established regional differences in obesity prevalence in the United States but relatively little is known about why or whether success in weight loss differs regionally. Objective: The objective of this study was to determine whether changes in body weight, engagement in physical activity (PA), and psychosocial factors differed in Alabama (AL) versus Colorado (CO) in response to a 16‐week behavioral weight loss program. Design: This is an ancillary study to a weight loss intervention being conducted simultaneously in AL and CO with identical intervention content and delivery in 70 participants ( n = 31 AL and n = 39 CO). Body weight, objective (accelerometry) PA, and responses to psychosocial questionnaires (reward‐based eating, stress, social support) were collected at baseline and at Week 16. Results: There were no differences in percent weight loss between states (AL: 10.98%; CO: 11.675%, p = 0.70), and weights at Week 16 were not different for participants in AL and CO (AL: 101.54 ± 4.39 kg, CO: 100.42 ± 3.67 kg, p = 0.84). Accelerometry‐derived step count, stepping time, and activity score were all greater at Week 16 for participants in AL compared to participants in CO. Hedonic eating scores were more favorable for participants in AL at baseline (AL: 24.08 ± 2.42; CO: 34.99 ± 2.12, p = 0.0023) and at Week 16 (AL: 18.62 ± 2.70; CO: 29.11 ± 2.19, p = 0.0023). Finally, participants in AL presented more favorable social support scores at Week 16 compared to participants in CO. Conclusions: Weight loss did not differ between states, suggesting that factors contributing to higher obesity rates in some regions of the United States may not be barriers to weight loss. Further, participants in AL experienced greater improvements in some factors associated with weight maintenance, indicating the need to study regional differences in weight loss maintenance. National Clinical Trial 03832933.